The Power of Focal Points Is Limited: Even Minute Payoff Asymmetry May Yield Large Coordination Failures - Crawford, Vincent P.; Gneezy, Uri; Rottenstreich, Yuval (The American economic review, 2008)
Since Schelling, it has often been assumed that players make use of salient decision labels to achieve coordination. Consistent with previous work, we find that given equal payoffs, salient labels yield frequent coordination. However, given even minutely asymmetric payoffs, labels lose much of their effectiveness and miscoordination abounds. This raises questions about the extent to which the effectiveness of focal points based on label salience persists beyond the special case of symmetric games. The patterns of miscoordination we observe vary with the magnitude of payoff differences in intricate ways that suggest nonequilibrium accounts based on "level-k" thinking and "team reasoning."